2013
DOI: 10.1002/mnfr.201300266
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of human cathelicidin antimicrobial peptide gene expression by vitamin D and stilbenoids

Abstract: Scope The cathelicidin antimicrobial peptide (CAMP) gene is induced by 1α,25-dihydroxyvitamin D3 (1α,25(OH)2D3), lithocholic acid, curcumin, nicotinamide and butyrate. Discovering additional small molecules that regulate its expression will identify new molecular mechanisms involved in CAMP regulation and increase understanding of how diet and nutrition can improve immune function. Methods and results We discovered that two stilbenoids, resveratrol and pterostilbene, induced CAMP promoter-luciferase expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Based on the evolutionarily-conserved nature of the steroid and nuclear receptor superfamily and the structural similarity that exists amongst resveratrol and other low-affinity, lipophilic VDR ligands, resveratrol was previously postulated and demonstrated experimentally by Guo and colleagues [43] to modulate intracellular VDR signaling. Independent investigations conducted by Jurutka and coworkers [26], as well as Dampf Stone and collaborators [7] revealed that resveratrol serves as an indirect modifier of the 1,25D-VDR signal transduction cascade, rather than serving as a direct VDR ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evolutionarily-conserved nature of the steroid and nuclear receptor superfamily and the structural similarity that exists amongst resveratrol and other low-affinity, lipophilic VDR ligands, resveratrol was previously postulated and demonstrated experimentally by Guo and colleagues [43] to modulate intracellular VDR signaling. Independent investigations conducted by Jurutka and coworkers [26], as well as Dampf Stone and collaborators [7] revealed that resveratrol serves as an indirect modifier of the 1,25D-VDR signal transduction cascade, rather than serving as a direct VDR ligand.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to synergistic effects, naturally occurring antimicrobial or immunomodulatory milk peptides may have an additional protective effect . Furthermore, the vitamin D content of milk may also be able to induce the expression of human antimicrobial peptides (AMPs) . In the past, a growing number of AMPs has been described, which are encrypted in the milk protein sequence, but released during fermentation or protein hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for the role of vitamin D in controlling the composition and activity of the gut microbiota may initially appear counter-intuitive. Guo et al [28] demonstrated that vitamin D regulates expression of an antimicrobial peptide, leading to the suggestion of using vitamin D to control bacterial diseases [29]. Secondary bile acids are made by intestinal bacteria, [30] and VDR is a receptor for the secondary bile acid lithocholic acid (LCA) which is hepatotoxic and a possible enteric cancer causing agent [31,32].…”
Section: Vitamin D and The Human Gut Microbiomementioning
confidence: 99%